Asian Development Outlook 2019 supplement Outlook steady even as trade tensions persist. (Asian Development Outlook., 2019)
Developing Asia is forecast to maintain strong but moderating growth in line with April forecasts in Asian Development Outlook 2019 (ADO 2019), even as trade conflict continues between the PRC and the US. The regional gross domestic product (GDP) is forecast to expand by 5.7% in 2019, as unexpectedly strong growth in Central Asia offsets small downgrades for East, South, and Southeast Asia in 2019, with growth slowing marginally to 5.6% in 2020. Excluding the newly industrialized economies of Hong Kong, China; the Republic of Korea; Singapore; and Taipei,China, the regional growth outlook is revised down slightly to 6.1% for 2019 and maintained at that rate for 2020.The combined growth forecast for the major industrial economies the US, the euro area, and Japan is maintained from ADO 2019. Upward revisions to growth prospects in the US are offset by downward adjustments to euro area growth forecasts.